B.) a=-5.7
1.6(a)=-9.12
(a)=(-9.12)/(1.6)
a=-5.7
I think you count the squares in the middle or radius ?
Answer:
3x^2y\sqrt(y)
Step-by-step explanation:
(\sqrt() means square root
its the 2nd one
Answer:
As per the question, we need to convert product of sum into sum of product,
Given:
(A' +B+C')(A'+C'+D)(B'+D'),
At first, we will solve to parenthesis,
= (A'+C'+BD) (B'+D')
As per the Rule, (A+B)(A+C) = A+BC, In our case if we assume X = A'+C', then,
(A' +B+C')(A'+C'+D) = (A'+C'+B)(A'+C'+D) = (A'+C'+BD)
Now,
= (A'+C'+BD) (B'+D') = A'B' + A'D' + C'B' +C'D' +BDB' +BDD"
As we know that AA' = 0, it mean
=A'B'+A'D'+C'B'+C'D'+D*0+B0
=A'B'+A'D'+C'B'+C'D' as B * 0 and D*0 = 0
Finally, minimum sum of product boolean expression is
A''B'+A'D'+C'B'+C'D'
=